2014
DOI: 10.1039/c4ob00986j
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free activation of methylene chloride and alkynes by amines in a three-component coupling reaction to synthesize propargylamines

Abstract: Propargylamines are synthesized via metal-free activation of the C-halogen bond of dihalomethanes and the C-H bond of terminal alkynes in a three-component coupling without catalyst or additional base and under mild reaction conditions. The dihalomethanes are used both as solvents as well as precursors for the methylene fragment (C1) in the final product. The scope of the reaction and the influence of various reaction variables has been investigated. A plausible reaction mechanism is proposed and the involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Its recrystallization from dichloromethane inadvertently resulted in (pyroH)[Cu(quin) 2 Cl] (3), a product, which confirms that pyrrolidine, initially present as a ligand in the copper(II) complex, reacted with the solvent. With dichloromethane, commonly employed as a solvent in synthesis and extraction processes, undesired reactions with primary and secondary aliphatic amines were observed previously, in particular when the solutions were left to stand for extended periods [43][44][45]. Later studies have confirmed that pyrrolidine rapidly reacts with dichloromethane at room temperature with the major products being 1,1 -methylenebis(pyrrolidine), known as aminal, and pyrrolidinium hydrochloride.…”
Section: Synthetic Considerationsmentioning
confidence: 83%
“…Its recrystallization from dichloromethane inadvertently resulted in (pyroH)[Cu(quin) 2 Cl] (3), a product, which confirms that pyrrolidine, initially present as a ligand in the copper(II) complex, reacted with the solvent. With dichloromethane, commonly employed as a solvent in synthesis and extraction processes, undesired reactions with primary and secondary aliphatic amines were observed previously, in particular when the solutions were left to stand for extended periods [43][44][45]. Later studies have confirmed that pyrrolidine rapidly reacts with dichloromethane at room temperature with the major products being 1,1 -methylenebis(pyrrolidine), known as aminal, and pyrrolidinium hydrochloride.…”
Section: Synthetic Considerationsmentioning
confidence: 83%
“…As sustainability is a significant concern in the chemical industry, the neat reaction is preferable, as it allows the assembly of complex compounds without the requirement for solvents. Furthermore, the reported AgNP‐catalyzed reaction was carried out smoothly at 25 °C, and proceeded at lower temperatures compared with previously reported AHA reactions …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the reported AgNP-catalyzed reaction was carried out smoothly at 25 8C, and proceeded at lower temperatures compared with previously reported AHA reactions. [45,46,48] With the optimized conditions in hand, the substrate scope of the AHA coupling reactionw as investigated ( Table 1). Dichloromethane, dibromomethane, diiodomethane, and dibromomethylbenzenea ll produced good results( Table S3 in the Supporting Information, entries 11 and 12, and Ta ble 1, 4b), and excellent yields were achieved when using cyclic,h eterocyclic, anda cyclica liphatic amines as the substrates (Table 1, 4a, 4l,a nd 4d).…”
Section: Catalytic Activity Of the Supported Catalysts In The Threecomentioning
confidence: 99%
“…On the other hand, a metal-free AHA reaction was also developed, but only moderate yields were obtained. 16 Moreover, as a special secondary amine, tetrahydroisoquinolines (THIQs) are found widely existed in natural products and have many biological activities. 17 Thus, many novel and valid methods were developed to synthesize THIQ derivatives, and most of them focused on the activation of THIQ's C1 atom.…”
Section: Introductionmentioning
confidence: 99%